(untitled) (Research, Society and Development, 2021)
This systematic review refers to the use of plants in medicine. For most of the population it is a search for an alternative cure. Articles published between 2000 and 2014 in three scientific databases: Academic Google, Scielo and Web of Science were subjected to analysis that was initially carried out by reading the title of the article, noting which mentioned terms related to herbal medicine. The articles selected in the first stage were analyzed by reading the Abstract, being selected those that mentioned some type of herbal treatment with the use of aloe vera L. Of these 36 articles, 8 in English and 28 in Portuguese. Currently, interest in the benefits of plants is growing in the field of homeopathy and herbal medicine. Among the most used is the aloe vera (Aloe vera). Present in both folk medicine and cosmetics.